Fluid geochemistry of the Cerro Galán geothermal system (Southern Puna, Argentina): Implications for the geothermal potential of one of the youngest giant calderas in the Andes - Chiodi, Agostina Laura (2024)
The exploration of novel geothermal systems, particularly those promising for electrical power generation, plays a fundamental role in incorporating new renewable sources into the energy matrix. Geothermal systems associated with volcanic calderas are considered ideal targets for exploration. This study focuses on the geochemical features of fluids from the Cerro Gal´an hydrothermal system, which is hosted within a major resurgent calderawith >3.5 Myr of magmatic evolution situated on the Southern Puna (Central Volcanic Zone of the Andes, NW Argentina). The main aim is constructing the first geochemical conceptual model and provide information on thegeothermal potential of this interesting resource. The main hydrothermal reservoir consists of a Na–Cl aquiferwith estimated temperatures up to 187 ◦C at depth. This reservoir is likely hosted within the fractured pre-caldera basement rocks, mainly including Miocene-Pliocene volcanic rocks and Proterozoic-Cambrian igneousand metamorphic rocks. The confinement of the deep reservoir is attributed to the deposits of the ToconquisGroup and Cueva Negra Ignimbrite, along with the basal section of the Cerro Gal´an Ignimbrite, which exhibit lowpermeability due to hydrothermal alteration. The presence of a phreatic explosion crater near one of the hotspring-rich areas is likely indicating past over-pressurization of the hydrothermal aquifer, resulting from efficientsealing. Furthermore, the absence of anomalous soil CO2 flux values on the top of the reservoir, except where thethermal spring discharges are located, can be explained by an effective cap-rock layer. Deep circulation ofmeteoric water, enriched with atmospheric gases, receives inputs of magmatic fluids (~11% of primordial he-lium), leading to the development of the hydrothermal Na–Cl aquifer. However, this deep fluid contributionmight be underestimated due to significant crustal assimilation (up to 50%) involved in the magma genesis of theCerro Gal´an Volcanic Complex, a process which modifies the He isotopic signature of the magmatic endmember.The hot springs, characterized by high flow rate (up to 459 m3/h) are positioned at the intersection between thecaldera margins and the NNE-SSW oriented tectonic structures, suggesting favorable permeability conditions.The preliminary geothermal gradient for the Cerro Gal´an area is estimated at around 98–101 ◦C/km. Such a highgradient can be attributed to the considerable heat flux generated by the transcrustal plumbing system of theCerro Gal´an caldera, which includes the shallow crystal mush reservoir (<4 km depth). The preliminarygeothermal potential of this giant caldera was performed using the volumetric method along with Monte Carlosimulations. The results indicate a probable power production capacity of 2.09 MWe and 10.85 MWe at 90 and50% confidence level, respectively. The results presented in this work constitute a foundational knowledge baseto promote a more advanced exploration phase for the geothermal resource. Additionally to the local energydemand, lithium and other metal mining operations, which are operating independently from the NationalInterconnected System, could potentially be interested in power generation through binary cycles.